Creation of the Language Center at Universidad Estatal de Bolivar, a curricular design proposal - Moreta Prado, Estuardo Napoleón (2007)
Because English is widely spoken, it has often been referred to as a "global language", the lingua franca¿ of the modern era. While English is not an official language in many countries, it is currently the language most often taught as a second language around the world. Some linguists believe that it is no longer the exclusive cultural sign of "native English speakers", but is rather a language that is absorbing aspects of cultures worldwide as it continues to grow. It is, by international treaty, the official language for aerial and maritime communications, as well as one of the official languages of the European Union, the United Nations, and most international athletic organizations, including the International Olympic Committee. Books, magazines, and newspapers written in English are available in many countries around the world. English is also the most commonly used language in the sciences. In 1997, the Science Citation Index reported that 95% of its articles were written in English, even though only half of them came from authors in English-speaking countries. The main problem was; the teaching-learning process of the English language at Universidad Estatal de Bolívar is applied only in the first academic year of all university¿s faculties without a curricular program in this scope. Therefore there are a very high percentage of teachers and students have their English limited. In addition, the University doesn¿t have a Language Center that leads to improve the achievement of the student¿s skills in the use of the English language or other languages. The present research work was a SOCIAL SURVEY technique because the research group was in touch with the reality in order to obtain reliable information in systematic and ordered way according to the research objectives. This information determined the students¿ needs of Universidad Estatal de Bolívar for foreign language learning, thereby thy demand for English learning as a second language. The information gathering technique that was used in the present work was the SURVEY. The QUESTIONNAIRE was used as an instrument of information gathering from a primary source. They were elaborated taking in consideration the formulated objectives in the research. This instrument was based on indicators to each question that allowed us to get real data...